Terapia breve intensiva com fonação em tubo de vidro imerso em água em mulheres com e sem afecção laríngea: ensaio clínico controlado e randomizado - Lima, Joziane Padilha de Moraes (2016)
Purpose: to verify and to compare aerodynamic vocal measures, from protocols of self-assessment, acoustic vocal changes of glottis source, singing voice range and vocal self-perception in women with and without laryngeal disorders who performed intensive short-term therapy through the technique of phonation into glass tube immersed in water; and the immediate effects of glottic source, aerodynamic measures and vocal self-perception. Methods: controlled and randomized clinical essay, with 46 women, in two groups, without laryngeal disorders (15) and with some type of disorders (nine). There was a control group, with the same group division, without disorders (13) and with disorders (nine). It was performed, in maximum phonation time, vital capacity, simple phonic coefficient, composed phonic coefficient, sound pressure level, vocal self-perception and singing voice range, before and after intensive short-term therapy of ten sessions. The technique was performed in six series of 15 repetitions. After the first session, it was collected the maximum phonation time of the vowel /a/, sound pressure level and the participants filled in a protocol of vocal self-perception. Results: in the group without laryngeal disorders, there was significant result in the following aspects: maximum phonation time of /a/, /u/, /z/, voiceless /e/, average of /a,i,u/ and numbers counting; relationships between /s/ and /z/ and obtained and expected maximum phonation time; reduction of the composed phonic coefficient and increase of the sound pressure level; average of frequency perturbation, shimmer in dB and percentage, amplitude perturbation quotient, degree of components and number of sub-harmonic segments and reduction of the lowest pitch in the singing range. In the group with disorders, there was improvement of maximum phonation time of voiceless /i/, /e/, average of /a,i,u/ and numbers counting; increase of sound pressure level; improvement of all perturbation measures of frequency and amplitude, higher fundamental frequency and standard deviation of the fundamental frequency. In the protocols, it was verified improvement of: hospital scale of anxiety and depression (anxiety); profile of participation and vocal activities (self-perception of their own vocal disorder severity, effects in emotion and work); scale of vocal symptoms (limitation, emotional, physical and total); quality of life and voice (emotional and total); voice handicap index (total). In both groups, there was improvement of self-perception. In the immediate effect, it was verified, in the group without disorders, improvement of absolute and percentage jitter, of perturbation relative average, of quotient of pitch perturbation and of degree of sub-harmonic components. There was increase of sound pressure level. In the group with disorders, there was improvement of the highest fundamental frequency; standard deviation of the fundamental frequency, in most frequency perturbation measures; shimmer in dB, soft amplitude perturbation quotient, and amplitude variation coefficient; increase of maximum phonation time of the vowel /a/. Conclusion: The technique provided acoustic improvement of glottic source, in the aerodynamic vocal measures, singing voice range, vocal self-perception and in the protocols of vocal self-assessment in the group with and without laryngeal disorders.